2021
DOI: 10.1101/2021.11.02.466885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Operon formation by insertion sequence IS3 in Escherichia coli

Abstract: Operons are a hallmark of the genomic and regulatory architecture of prokaryotes. However, the mechanism by which two genes placed far apart gradually come close and form operons remains to be elucidated. Here, we propose a new model of the origin of operons: Mobile genetic elements called insertion sequences can facilitate the formation of operons by consecutive insertion-deletion-excision reactions. This mechanism barely leaves traces of insertion sequences and is difficult to detect in evolution in nature. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…The adaptation and evolution of C. striatum can be explained by the insertion sequences. In Escherichia coli , it has been suggested that IS could be associated with the genome evolution, fitness, and the formation of new operons ( Gaffé et al, 2011 ; Consuegra et al, 2021 ; Kanai et al, 2021 ). This raises the question if the presence of IS would explain the transition of C. striatum lineages from normal microbiota to the generation of pathogenic lineages, and whether it would also be related to the role of the environment in the evolution of its pathogenicity.…”
Section: Why Should Insertion Sequences Be An Epidemiological Descriptor?mentioning
confidence: 99%
“…The adaptation and evolution of C. striatum can be explained by the insertion sequences. In Escherichia coli , it has been suggested that IS could be associated with the genome evolution, fitness, and the formation of new operons ( Gaffé et al, 2011 ; Consuegra et al, 2021 ; Kanai et al, 2021 ). This raises the question if the presence of IS would explain the transition of C. striatum lineages from normal microbiota to the generation of pathogenic lineages, and whether it would also be related to the role of the environment in the evolution of its pathogenicity.…”
Section: Why Should Insertion Sequences Be An Epidemiological Descriptor?mentioning
confidence: 99%